2012
DOI: 10.1007/s12639-012-0151-y
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasitic infection in Bhil tribe of Rajasthan, India

Abstract: A total of 224 Bhil tribal individuals (115 males and 109 females) of different age groups inhabiting tribal rural areas of Udaipur district of Rajasthan, India were investigated for the prevalence of intestinal parasitic (protozoan and helminths) infections. Fresh stool samples of these tribal subjects were examined microscopically by direct wet smear with saline and 1 % Lugol's iodine and formaline ether concentration. Of these 116 (51.78 %) were found to be infected with diverse species of intestinal parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 7 publications
7
19
3
Order By: Relevance
“…The study conducted in Udaipur among the individuals of Bhil tribe [27] showed a high isolation rate of about 51.78% as compared to this study. Such differences may occur due to the varied socioeconomic conditions of different communities.…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations
“…The study conducted in Udaipur among the individuals of Bhil tribe [27] showed a high isolation rate of about 51.78% as compared to this study. Such differences may occur due to the varied socioeconomic conditions of different communities.…”
Section: Discussioncontrasting
confidence: 48%
“…Such variations may be due to equal involvement of females in outdoor activities as compared to males nowadays. In various studies, the most common age group involved was 6-20 years [14,18,19,27] as compared to this study, where it is 31-40 years. In a previous study also, the trend of parasitic infection in recent years has shown to predominate among adults as compared to children [9].…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…These samples were processed for wet film preparation using 1 % Lugol's iodine and formalin ether concentration technique (Paniker 2002) for the evidence of protozoan and helminthic infection (Choubisa et al 2012). Identification of ova, cysts, trophozoites and larvae of these parasites was made on the basis of morphological features (Soulsby 1982).…”
Section: Methodsmentioning
confidence: 99%